KAJIAN MORFOLOGI KOTA BALIKPAPAN - Abdul Mattin; Agus Fitrianto; Suheriah Mulia Devi (Display Architecture Journal, 2022)
Balikpapan City is a city located on the shores of Balikpapan Bay which has abundant biodiversity and natural resources. The city has undergone continuous urban spatial structure changes. Starting from a fishing area, then becoming an oil and gas industrial city, continued as an urban support for the New State Capital. This study aims to find the spatial structure pattern of the city of Balikpapan using the morphological approach of the city of Balikpapan. The method used is a historical approach from the study of past literature and Analysis of the Geographic Information System of the city of Balikpapan. This study found that the linear shape of the city follows the waterfront of the Balikpapan bay, the morphology of the city structure is oriented to the economic center, namely the Pertamina refinery, and the visual morphology of the city of Balikpapan does not have special landmarks other than the Islamic center mosque, sport center dome, and Balikpapan stadium.